Severe biventricular thrombosis in eosinophilic granulomatosis with polyangiitis: a case report. Issue 6 (5th November 2020) - Hamudi, Jihad; Karkabi, Basheer; Zisman, Devy; Shiran, Avinoam
Abstract: Background: Eosinophilic granulomatosis with polyangiitis (EGPA), formerly known as Churg–Strauss syndrome, is a rare multisystem disease characterized by asthma, rhinosinusitis, and eosinophilia. Cardiac involvement, present in half the patients, may be life threatening. Case summary: A young woman with long-standing asthma and nasal polyposis was admitted with new-onset dyspnoea, sinus tachycardia, and eosinophilia. She had severe biventricular thrombosis and severe tricuspid regurgitation (TR) on echocardiography, with preserved ejection fraction of both ventricles. Cardiac magnetic resonance (CMR) imaging showed diffuse subendocardial late gadolinium enhancement (LGE). She had a positive test for perinuclear antineutrophil cytoplasmic antibodies (p-ANCA) confirming the diagnosis of ANCA positive EGPA. She was treated with anticoagulation, high-dose corticosteroids, cyclophosphamide, and rituximab with gradual resolution of her symptoms. Follow-up echocardiography showed significant improvement in ventricular thrombi and TR but could not reliably exclude residual ventricular thrombus. Repeat CMR at 11 months confirmed complete resolution of both ventricular thrombi and near complete resolution of LGE. Discussion: Cardiac involvement in EGPA, a rare cause of heart failure, can manifest as severe biventricular thrombosis and severe TR, resulting in heart failure with preserved ejection fraction. Combined immunosuppression and anticoagulation can lead to complete remission within a year. CMR is instrumental for both diagnosis and follow-up of EGPA, allowing for safe discontinuation of oral anticoagulation.